Construction of Innovation Behavior of College-Student Entrepreneurs Using Entrepreneurship and Innovation Theory Under Educational Psychology - Zhang, Baoge; Han, Song; Xu, Qiuyan; Jiao, Lan (Frontiers in Psychology, 2021)
The purpose is to analyze the entrepreneurship and innovation education of colleges from the perspective of educational psychology and optimize the teaching mode reform of entrepreneurship and innovation courses. Here, theoretical research and case studies are combined to explore the performance of college-student entrepreneurs during college and work and have provided data for targeted entrepreneurship and innovation education in schools. Meanwhile, the specific manifestation of the entrepreneurial spirit during work is analyzed, and the impact of entrepreneurial spirit is discussed on new venture performance. The case study shows that most of the surveyed college-student entrepreneurs have a higher educational background and short venture-creation time, and their ventures are mostly small and medium-sized enterprises (SMEs) with rapid development. Most entrepreneurs show strong entrepreneurial spirit during college, and the scores of each dimension are higher than 3.5. Among them, the average score of honesty is 3.85. Entrepreneurs have high scores in innovation spirit and honesty in extracurricular practice, so schools should focus on the cultivation of honesty and innovation spirit. At work, the surveyed entrepreneurs have high innovation attitude and innovation intention, both averaging about 3.5 points. The results of in-depth interviews show that most entrepreneurs use innovative methods to solve practical problems in their work, and innovation spirit plays an important role in improving venture performance. According to the hypothesis test results, innovation attitude and innovation performance have a significant positive impact on innovation behavior. The content is fully inclusive, the research is comprehensive, and the results have very important application value. The results can provide scientific and effective references for colleges to reform entrepreneurship and innovation education.